(untitled) (Interdisciplinary Studies Journal, 2023)
Social vulnerability and human development are indicators related to the socioeconomic, political and environmental field, capable of characterizing the level of social prosperity of a population in a given context, unveiling evils and at the same time subsidizing the planning of policies that will favor the well-being of the collectivity. In this sense, the study aims, from the discussion of the interface between the Social Vulnerability Index (IVS) and the Human Development Index (HDI), to analyze the level of social prosperity of RIDE – Petrolina/Juazeiro. As a methodological procedure, this work uses bibliographic-documentary research, starting with the collection of data in virtual and institutional databases such as IPEA (Atlas of Social Vulnerability/Atlas Brazil) and IBGE, and analyzing specific indicators with basic descriptive statistics and the support of RStudio and LibreOffice Calc software. Its results bring important reflections on the role of public policies and their management, aiming at the reduction of social inequalities. It was found that its level of prosperity was very low in 2000, becoming medium after a decade (2010), based on the reduction of the IVS and the growth of the IDHM.